High‐performance visible and near‐infrared dual‐band photodetector based on anisotropic 2D NbS3 with perpendicularly reversed polarization behaviors - Jidong Liu; Haibo Gan; Qiaoyan Hao; Yonghong Zeng; Youning Gong; Jiaqi Zhu; Jiarui Huang; Fei Liu; Wenjing Zhang (InfoMat)
Abstract Dual‐band photodetectors exhibit considerable advantages in target discrimination and navigation compared to single‐band devices in complex circumstances. However, it remains a major challenge to overcome the limitations of traditional devices in terms of their integration with multiple light‐absorbing layers and complicated optical components. In this study, a visible and near‐infrared (NIR) dual‐band polarimetric photodetector with a single light‐absorbing layer is constructed by utilizing the distinctive conversion of linear dichroism (LD) polarity in two‐dimensional niobium trisulfide (NbS3). The NbS3 photodetector exhibits selective detection behaviors in the visible and NIR bands, in which by switching the polarization angle of the incident light from 0° to 90°, photocurrent decreases in the visible region, and increases in the NIR region. Specifically, the degrees of linear polarization of photocurrent are 0.59 at 450 nm and −0.47 at 1300 nm, respectively. The opposite photoresponse in the visible and NIR bands of the photodetector significantly enhances the dual‐band information recognition. Therefore, clear visible and NIR dual‐band polarimetric imaging is accurately realized based on the NbS3 photodetector taking advantage of its fast response speed of 28 μs. Such anisotropic materials, with unique LD conversion features, can facilitate selective modulation between the visible and NIR spectral ranges and promote the development of next‐generation multi‐dimensional photodetection for various applications, including com/puter vision, surveillance, and biomedical imaging.